IMPLEMENTASI MODEL FORENSIC AWARE ECOSYTEM FOR IOT (FAIOT) PADA PURWARUPA RUMAH PINTAR BERBASIS INTERNET OF THINGS (IOT) - Eri Haryanto; Agustin Setiyorini (Informasi Interaktif, 2021)
The internet network that connects many computers in the world has now reached almost all regions in Indonesia. IoT is a technology concept consisting of objects that are connected to each other via an internet network that has a special address and can communicate with each other which gives birth to various types of smart systems such as smart homes, smart farms, smart cities, smart building, smart health, smart transport, and smart environments. other.This study designs a smart home application model that is designed in such a way as to be equipped with the FAIoT model. This research has a specific objective, namely to apply the FAIoT model to a smart home application prototype, then run a case simulation on a smart home application and analyze the resulting digital artifacts as a consideration in proving a case. Based on the results of the analysis and observations of the forensic IoT devices in the form of two smart houses that were targeted by the attackers, it shows that system activity is stored properly on the FAIoT platform. The results of the analysis prove that the attack on IoT devices in the form of two smart houses can reveal the facts of the case based on findings that are used as digital evidence. In addition to the fact findings from the cases that occurred in this study, the Internet of Things (IoT) environment with the FAIoT Model has been successfully developed in this study, which can be used as research objects.Keywords: Smarthome, Internet of Things, IoT forensic, IoT Security